2015
DOI: 10.1103/physrevlett.115.025002
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Plasma Polarizer: Impact of Temperature Anisotropy on Relativistic Transparency

Abstract: 3D particle-in-cell simulations demonstrate that the enhanced transparency of a relativistically hot plasma is sensitive to how the energy is partitioned between different degrees of freedom. For an anisotropic electron distribution, propagation characteristics, like the critical density, will depend on the polarization of the electromagnetic wave. Despite the onset of the Weibel instability in such plasmas, the anisotropy can persist long enough to affect laser propagation. This plasma can then function as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 56 publications
2
33
1
Order By: Relevance
“…Therefore, the analysis is well suited to make meaningful predictions regarding electron acceleration in near-critical and over-critical plasmas, provided that such plasmas are relativistically transparent to the incoming high-intensity laser pulse 28,29 . However, wave propagation becomes a crucial aspect in this case and it should be addressed selfconsistently 30 taking into account transverse laser pulse dimensions and its polarization 31,32 .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Therefore, the analysis is well suited to make meaningful predictions regarding electron acceleration in near-critical and over-critical plasmas, provided that such plasmas are relativistically transparent to the incoming high-intensity laser pulse 28,29 . However, wave propagation becomes a crucial aspect in this case and it should be addressed selfconsistently 30 taking into account transverse laser pulse dimensions and its polarization 31,32 .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The physics underpinning relativistic induced transparency (RIT) in thin foils is discussed by Vshivkov et al [15]. It has been shown that the effect can modify the rising edge profile, duration and polarization of the laser pulse [16][17][18][19] and that it is important in driving new ion acceleration [20,21] and radiation production [22][23][24] mechanisms.For the first time, we demonstrate that an ultraintense laser pulse induces a 'relativistic plasma aperture' in a thin foil and as a result undergoes the fundamental optic 2 process of diffraction. It is demonstrated, both numerically and experimentally, that the collective electron motion (including angular frequency of rotation) is determined by the resulting near-field diffraction pattern and can be controlled by simply varying the polarization of the laser.…”
mentioning
confidence: 99%
“…The stripes are in fact slightly curved, consistent with a small rotation of the diffraction pattern. An examination of the laser polarization at different points along the X-axis shows that it changes from linear to slightly elliptical when transmitted through the plasma aperture.Anisotropy induced in the heating of the target electrons by a linearly polarized pulse can cause transient effects such as a difference in phase velocities in the two orthogonal directions, which can induce a degree of ellipticity in the polarization [19]. This effect accounts for the slight rotation in the diffraction pattern.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a recent surge of interest in using laserplasma optical systems to manipulate the basic properties of light waves [1][2][3][4]. Plasma-based photonic devices are attractive because they can be ultrafast, damageresistant, and easily tunable.…”
mentioning
confidence: 99%